PENGARUH LEVERAGE, PROFITABILITY DAN INDEPENDENT BOARD OF COMMISSIONERS TERHADAP MANAJEMEN LABA - Jhonatan, Jessica; Suhendah, Rousilita (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The purpose of this research is to know the effects of leverage, profitability and independent board of commissioners on earnings management in mining, transportation, infrastructure, utilities, and agricultural industry listed on the Indonesia Stock Exchange during 2017-2020. This research using 18 kinds of sample on mining, transportation, infrastructure, utilities, and agricultural industry with 4 years period. Sample was process by Eviews 12.0 and Microsoft Excel with selected sampling by using purposive sampling method. The results of this study show that leverage and profitability have a significant effect on earnings management and independent board of commissioners does not have a significant affect earnings management on mining, transportation, infrastructure, utilities, and agricultural industry. This research can useful for company and investor for analyzing factors that influence earnings management.